1994
DOI: 10.1016/s0886-3350(13)80651-7
|View full text |Cite
|
Sign up to set email alerts
|

Relative strength of scleral corneal and clear corneal incisions constructed in cadaver eyes

Abstract: Square scleral corneal, square clear corneal, and rectangular clear corneal incisions were constructed in six cadaver eyes that had no previous intraocular surgery. The 3.2 mm or smaller wounds had sutureless closures. To determine their relative abilities to resist leakage and iris prolapse, eyes were tested at external pressures of up to 525 pounds per square inch (psi) at one of two intraocular pressure (IOP) ranges: 10 to 15 mm Hg or 20 to 25 mm Hg. The square scleral corneal (3.2 mm x 3.2 mm) and square c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 5 publications
0
29
0
5
Order By: Relevance
“…A square wound affords greater stability than a rectangular wound [9]. In this study, a square side-port corneal incision was noted to rarely leak, even without hydration.…”
Section: Discussionmentioning
confidence: 60%
“…A square wound affords greater stability than a rectangular wound [9]. In this study, a square side-port corneal incision was noted to rarely leak, even without hydration.…”
Section: Discussionmentioning
confidence: 60%
“…[5][6][7][8][9][10][11][12][13][14] Many consider stromal hydration to be an important adjunct that may be used to improve wound integrity in the early postoperative period, with both in vitro and in vivo studies suggesting a possible benefit. 5,6,9,10,12,13 Wong A developed a novel modification of the CCI that provides an enhanced effect of stromal hydration and wound sealing. To our knowledge, this study is the first prospective trial comparing anterior stromal pocket hydration and conventional hydration and shows a significant advantage for this modified technique in preventing wound leak caused by direct pressure to the area of the incision, particularly the posterior lip of the CCI.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] However, Kohnen and Kaspar 31 also showed minimum enlargement (2.8%) when an SA60 IOL was implanted with a Monarch II/cartridge C, as done in our study. Ernest et al 35,36 and Mackool and Russell 37 found incision size has a direct impact on the strength and stability of CCIs and, thus, on the risk for endophthalmitis. [35][36][37] All our incisions were located superiorly.…”
Section: Discussionmentioning
confidence: 99%